A COMPARATIVE STUDY OF DRAINAGE OF BREAST ABSCESS BY CONVENTIONAL INCISION AND DRAINAGE VERSUS SUCTION DRAINAGE VERSUS ULTRASOUND-GUIDED NEEDLE ASPIRATION - CHORMA, ANKIT; PARGI, ARUN KUMAR; YADAV, RINKU (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: Breast abscesses are common among lactating women most prevalent in developing countries because of poor hygiene, malnutrition, and health conditions. In era of technical advances management of breast abscess has shifted to minimally invasive and painless techniques which are more patient friendly. This study compare outcomes in management of breast abscess by ultrasound-guided needle aspiration, suction drainage, and incision and drainage procedure. Methods: The present study was conducted in department of surgery in collaboration of MGM Medical College Indore with Government Medical College, Khandwa. A total 120 patients of breast abscess were divided in three groups. One group was managed by incision and drainage second group by suction drainage and third group by ultrasound-guided needle aspiration (40 patients in each group). Results: In our study, total 120 patients were analyzed, majority of the cases (40.8%) belong to 21–25 years age group. Post-operative pain, high recurrence rate, fistula formation, cessation of breast feeding, ugly scar formation, and longer duration of hospital stay were observed in incision and drainage procedure. Conclusions: USG-guided needle aspiration was the safest, cost effective, and widely accepted procedure in the treatment of breast abscess as compared to incision and drainage.